How to predict the 2014 World Cup winner (in one simple equation): determinants of national football team results 2011-2013 - a new methodology - Scelles, N.; Andreff, W. (Fraser of Allander Institute Economic Commentary, 2014)
This short note sets out an approach to predicting national football team results using a new, hybrid economics-based methodology. It draws on previous work in the field and was tested on almost 3,000 international football matches over the period 2011- 2013. The same methodology can be used in a predicative way and could be used, for example, to predict the result of the 2014 World Cup in Brazil. A forthcoming article to be published by the Fraser Economic Commentary will seek to predict Scotland`s likely progress in the forthcoming Euro 2016 competition.